1981
DOI: 10.1364/ao.20.002220
|View full text |Cite
|
Sign up to set email alerts
|

Optical pulse propagation through clouds

Abstract: The cloud impulse response (spatial and temporal) to optical pulse propagation has been measured. Experimental data are reported for the radiance function, pulse stretching, and (the first published) delay time. The results have been confirmed by Monte Carlo modeling. A geometric scattering model is presented explaining the temporal results for the test conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…If light reaches the observer through forward scattering, it will not have been delayed significantly or distorted. Matter and Bradley [] show experimentally with 10 ns laser pulses that clouds of optical depth 8 to 20, in a path length of 765 m, do not significantly delay or distort the laser pulse for observations made in the direction of the laser and 10° away from that direction. On the other hand, Bucher and Lerner [] sent laser pulses through higher optical depth clouds than Matter and Bradley [] and measured a time spreading of the laser pulse up to 10 µs observed up to 45° off axis to the laser.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If light reaches the observer through forward scattering, it will not have been delayed significantly or distorted. Matter and Bradley [] show experimentally with 10 ns laser pulses that clouds of optical depth 8 to 20, in a path length of 765 m, do not significantly delay or distort the laser pulse for observations made in the direction of the laser and 10° away from that direction. On the other hand, Bucher and Lerner [] sent laser pulses through higher optical depth clouds than Matter and Bradley [] and measured a time spreading of the laser pulse up to 10 µs observed up to 45° off axis to the laser.…”
Section: Discussionmentioning
confidence: 99%
“…Matter and Bradley [] show experimentally with 10 ns laser pulses that clouds of optical depth 8 to 20, in a path length of 765 m, do not significantly delay or distort the laser pulse for observations made in the direction of the laser and 10° away from that direction. On the other hand, Bucher and Lerner [] sent laser pulses through higher optical depth clouds than Matter and Bradley [] and measured a time spreading of the laser pulse up to 10 µs observed up to 45° off axis to the laser. Bucher and Lerner [] observed that maximum laser signal reception and the fastest received signal risetime were in the direction to the laser, but even those signals had a decaying tail attributed to multiple scattering.…”
Section: Discussionmentioning
confidence: 99%
“…[]. In all cases herein we estimate that the photons are scattered through angles of less than 10 o as seen from the camera; based on Bucher and Lerner [] and Matter and Bradley [] the delay caused by scattering for these cases may be up to 3 µs and has not been included in T D10 . Scattering will also lengthen the overall duration of the luminosity increases, but in our cases this effect is small relative to our 20 µs time window of the video data.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Guo and Krider () offered a generic sense of what the initial portion of lightning's unobscured optical emission looks like, but a single canonical estimate is unlikely representative of natural breadth, leaving us limited in our understanding of the optical “truth term” for different lightning processes. Attempts have therefore likewise been made to address the stochastic scattering process and to dredge a unique source term from propagated signals (Davis & Koshak et al, ; Light et al, ; Marshak, ; Matter & Bradley, ; Thomason & Krider, ). Statistical comparison of scattered light with models confirms that the process is one of modified diffusion and that unfortunately the consequences of the multiple scatterings are non‐unique (Light et al, ).…”
Section: General Forte Optical Findingsmentioning
confidence: 99%